The Efficacy of Percutaneous Transhepatic Gallbladder Drainage Combined with Gallbladder-Preserving Cholecystolithotomy in High-Risk Patients with Acute Calculous Cholecystitis - Kang C; Zhang J; Hou S; Wang J; Li X; Li X; Chi X; Shan H; Zhang Q; Liu T (Dove Medical Press, 2022)
Chunbo Kang, Jie Zhang, Shiyang Hou, Jinlei Wang, Xubin Li, Xiaowei Li, Xiaoqian Chi, Haifeng Shan, Qijun Zhang, Tiejun Liu General Surgery Department, Beijing Rehabilitation Hospital of Capital Medical University, Beijing, 100144, People's Republic of ChinaCorrespondence: Tiejun Liu, General Surgery Department, Beijing Rehabilitation Hospital of Capital Medical University, Xixiazhuang, Badachu Road, Shijingshan District, Beijing, 100144, People's Republic of China, Tel/Fax +86 10 5698 1152, Email liutjdoc@163.comObjective: This study aimed to investigate the value of combining percutaneous transhepatic gallbladder drainage (PTGD) with gallbladder-preserving cholecystolithotomy (GPC) in high-risk patients with acute calculous cholecystitis.Methods: Clinical data from 74 high-risk patients with acute calculous cholecystitis, admitted to our hospital between October 2018 and September 2021, were analyzed retrospectively. All the patients underwent PTGD, and 59 of them underwent delayed cholecystectomy, while 14 patients were subjected to GPC 8- 12 weeks after the PTGD; one patient, whose life expectancy was fewer than 6 months, was not treated for gallstones after PTGD.Results: In all 74 patients, symptom remission was achieved after the PTGD therapy, and the incidence of catheter-related complications was 10.8%. Among the 59 patients who underwent delayed cholecystectomy (DC) after PTGD, there was a complication incidence of 6.8%. Of the 14 patients who underwent GPC after the PTGD, 13 patients were subjected to the removal of drainage tubes, 1 patient received cholecystostomy catheter draining externally, and two patients (14.3%) had complications. There were no perioperative deaths.Conclusion: Percutaneous transhepatic gallbladder drainage, combined with GPC, is a safe and effective treatment that is suitable for high-risk patients with acute calculous cholecystitis who cannot receive DC. This combined method allows for early acute cholecystitis to settle, helps to remove gallstones at a later stage, and solves the problem of long-term tube drainage after PTGD.Keywords: percutaneous transhepatic gallbladder drainage, PTGD, gallbladder-preserving cholecystolithotomy, GPC, high-risk acute calculous cholecystitis